2017
DOI: 10.18494/sam.2017.1421
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Seasonal Variations of Dynamic Characteristics of a Concrete Bridge by Employing a Wireless Acceleration Sensor Network System

Abstract: In this study, a fundamental application of a wireless acceleration sensor network system was carried out by conducting two bridge vibration experiments in autumn and winter. Seasonal effects on the dynamic characteristics of a multispan ballasted prestressed concrete railway bridge were investigated by employing a wireless acceleration sensor network system as a basic study of structural health monitoring technology. The dynamic parameters of every single span, such as natural frequencies, damping ratios, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…12, the natural frequencies in each mode from the No.1 to No.8 experiments show a clear seasonal variation tendency that there are two local maximum peaks of the natural frequencies in the Februaries of 2016 and 2017. To find reasonable explanations for this phenomenon, we have carried out a series of investigations [16,27,28]. Because Hokkaido is in the northern hemisphere, the season in February is winter.…”
Section: Vibration Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…12, the natural frequencies in each mode from the No.1 to No.8 experiments show a clear seasonal variation tendency that there are two local maximum peaks of the natural frequencies in the Februaries of 2016 and 2017. To find reasonable explanations for this phenomenon, we have carried out a series of investigations [16,27,28]. Because Hokkaido is in the northern hemisphere, the season in February is winter.…”
Section: Vibration Experimentsmentioning
confidence: 99%
“…Ubertini et al [14] investigated the environmental effects on a tower and proposed a method to remove the effect. For the ballasted railway bridges, by monitoring the dynamic behavior of the bridge, the effect of frozen ballasts on the natural frequencies is found [15,16]. To briefly explain the mechanism of the environmental effect on the modal properties, the modulus of elasticity of the construction materials varies owing to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a simulation experiment on the design of an aluminum bridge showed that this method could identify the abnormal changes in the bridge. (11) The natural frequency of a bridge can be selected as an indicator for bridge damage identification, (12) which has the advantage of easy measurement. Mode recognition can be used for this method.…”
Section: Introductionmentioning
confidence: 99%